First report of a rickettsia-like organism from farmed Chinook salmon, Oncorhynchus tshawytscha (Walbaum), in New Zealand. Issue 3 (3rd July 2017) - Brosnahan, C. L.; Ha, H. J.; Booth, K.; McFadden, A. M. J.; Jones, J. B.
ABSTRACT: In the summer months of 2015 Chinook salmon, Oncorhynchus tshawytscha (Walbaum), were submitted to the New Zealand Ministry for Primary Industries (MPI) for disease investigation. Gross examination of 10 moribund fish revealed multiple areas of ulceration over all areas of the body including fins and mouth in eight of the 10 fish. Pale livers ( n  = 4), mottled appearance of the kidney ( n  = 5) and reddening of the distal intestines ( n  = 5) were also observed. As these fish presented with skin lesions, Piscirickettsia salmonis was included as a differential diagnosis. Testing for this agent was conducted and a rickettsia - like organism (RLO) was detected by histopathology in seven fish and by molecular methods in three fish. Nucleic acid sequencing revealed that this organism had highest similarity to a piscirickettsia-like organism with a 19 base pair (bp) deletion in the internal transcribed spacer (ITS) region of the rDNA operon when compared to the reference strain P. salmonis, LF-89 (ATCC VR-1361). The variation was similar to that of the Tasmanian RLO detected in Atlantic salmon, Salmo salar L (GenBank accession number AY578985). Based on these sequence variations, a tentative identification of New Zealand rickettsia-like organism (NZ-RLO) was suggested. NZ-RLO is not considered to be the primary cause of the mortalities in these fish, with the primary cause still under investigation. This is the first report of a RLO in New Zealand farmed salmon.